The Christmas drama of the household of St John's College, Oxford - Dutton, Elisabeth (Manchester University Press, 2019)
This chapter considers early modern academic drama performed at St John's College, Oxford. Dutton begins by describing the college household materials on which such performances drew, adopting a productively broad definition of this category that includes the people working, studying, and teaching at St John's, as well as their immediate neighbours in town; the college's domestic furnishings, such as tables, paintings, and candles; the matter covered there in lectures; and the university's own medieval foundations. Working first from a text now known as The Christmas Prince, a richly informative but often overlooked account of the 1607-1608 Christmas festivities at St John's, Dutton describes the financing of the St John's plays as well as the practicalities associated with their staging and rehearsal and with the sourcing of actors. In the productions performed as part of the Christmas Prince celebrations as well as in the earlier and later examples of St John's college drama that Dutton examines, the college play emerges as a means of reaffirming and celebrating the local, collegiate culture as well as constituting an interface with the outside world across which people and ideas might move both into and out of the college household.